2015
DOI: 10.1080/15384101.2015.1014147
|View full text |Cite
|
Sign up to set email alerts
|

The emerging role of lysine demethylases in DNA damage response: dissecting the recruitment mode of KDM4D/JMJD2D to DNA damage sites

Abstract: KDM4D is a lysine demethylase that removes tri-and di-methylated residues from H3K9 and is involved in transcriptional regulation and carcinogenesis. We recently showed that KDM4D is recruited to DNA damage sites in a PARP1-dependent manner and facilitates double-strand break repair in human cells. Moreover, we demonstrated that KDM4D is an RNA binding protein and mapped its RNA-binding motifs. Interestingly, KDM4D-RNA interaction is essential for its localization on chromatin and subsequently for efficient de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 104 publications
0
26
0
Order By: Relevance
“…7 This mutant, which can no longer bind RNA, failed to accumulate at DNA damage sites, indicating that KDM4D-RNA interaction is required for its DNA damage accumulation. 6 Altogether, these studies implicate PARP1 and yet unidentified RNA molecules in regulating KDM4D function in the DDR.…”
mentioning
confidence: 92%
See 3 more Smart Citations
“…7 This mutant, which can no longer bind RNA, failed to accumulate at DNA damage sites, indicating that KDM4D-RNA interaction is required for its DNA damage accumulation. 6 Altogether, these studies implicate PARP1 and yet unidentified RNA molecules in regulating KDM4D function in the DDR.…”
mentioning
confidence: 92%
“…KDM4D PAR-binding region was mapped to residues 350-474. 6 This region contains the residues (E357/R450/R451/R455) that are essential for KDM4D PARylation and assembly at sites of DNA damage. 4 A fragment of KDM4D (residues 1-474), containing the PAR-binding domain (residues 350-474), showed a minor and transient accumulation at DNA damage sites.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies showed that KDM4D can be swiftly recruited to DNA damage sites in a PARP1-dependent manner and facilitate double-strand break repair in human cells, which ensure efficient repair of DNA lesions to maintain genome stability [20,21]. KDM4D is also a novel cofactor of androgen receptor since it interacts with androgen receptor and stimulates its ability to up-regulate transcription, which plays an indispensable role in prostate cancer [22].…”
Section: Introductionmentioning
confidence: 99%